Nexus Between Economic Development and Population: Empirical Evidence from Pakistan - Afreen, Khawar; Khan, Afaq Ali; Khan, Muhammad Wajid (iRASD Journal of Economics, 2024)
The article explores the real-world connection involving population increase and economic development in Pakistan. This research examines the long-run and short-run implications of demographic parameters like population expansion, expectancy of life and fertility rate on the advancement of the Pakistani economy. The theoretical foundation of the study is built on demographic change, which takes into account life expectancy and the birth rate in the production function, as well as human capital development to establish research goals. The current study used Pakistan's time-series information from 1981 to 2021. The dataset was retrieved using the World Development Indicator engaging the Auto Regressive Distributed Lag model (ARDL) to figure out the short and long-run interactions between prosperity and population increase. The outcomes demonstrate an adverse and substantial association between the expansion of the population with the growth in the economy. On the contrary, life expectancy has a large and favourable impact on the development of the economy. According to the results, population growth has a detrimental impact on the development of the economy; nevertheless, appropriate usage of these assets must be made. Whenever a nation maintains an extensive population and fails to utilize its strength effectively, then it will become a strain on the economy. The authorities ought to implement comprehensive strategies for improving employment opportunities in the entire nation. Though Pakistan possesses an intelligent workforce, the challenge remains how to harness its potential profitably.